Determinación del porcentaje de remediación del bocashi para suelos contaminados por glifosato, mediante un sistema combinado de aireación y biopilas en cultivos asociados de café y cacao en el barrio San Roque de la parroquia Pachicutza, cantón El Pangui, provincia Zamora Chinchipe - Guerrero Encalada, Gomer Guillermo (2016)
The present study aims to remedy soils altered by the pollution caused by agricultural activities in the production of coffee and caco by the dumping of glyphosate in the soil in the San Roque neighborhood in the province of Zamora Chinchipe. The ex - situ study was carried out in the San Roque neighborhood in the production of organic fertilizer and in the city of Zamora the implementation of the experimental trial. For the following study the bocashi fertilizer was made, performing temperature, humidity and pH controls during fertilizer fertilization. Then, four plots were constructed, where the treatment with its repetition and the witnesses were implemented, then the aeration system was installed in the treatment with its repetition, the material added in the treatment with its repetition was 20 kg of fertilizer plus 50 kg of contaminated soil, performing constant monitoring During the 3 months of the experimental trial. At the conclusion of the experimental test, a composite sample of the treatment with its repetition and a composite sample of the controls were collected, analyzing the texture, organic matter, nitrogen, phosphorus, potassium, pH, and glyphosate. At the end of the study, it was concluded that the bocashi fertilizer in the soil significantly improves all the parameters mentioned above except for glyphosate, which was determined that in the treatment with their repetition they showed a removal of 90% of glyphosate in the soil, compared With the initial sample and the control, which showed the same level of concentration of glyphosate in the soil.